Physical exercise and COVID-19 pandemic vs. PubMed: two-months of dynamics and one-year of original scientific production - Vancini, R. L.; Andrade, M. S.; Viana, R. B.; Nikolaidis, P. T.; Knechtle, B.; Campanharo, C. R. V.; de Almeida, A. A.; Gentil, P.; de Lira, C. A. B. (Sports Medicine and Health Science, 2021)
Our aim was to conduct a narrative review about physical exercise and Corona Virus Disease 2019 (COVID-19). A literature search was completed crossing the keywords "COVID-19" and "physical exercise", for a narrative review, and physical activity (PA), physical exercise, physical training, sport, physical fit-ness, for a systematic review; search strategy (Randomized Controlled Trial, in the last 1 year, English). The first search date was closed on 04/26/2020 and 06/26/2020. This strategy was chosen to assess the dynamics of scientific in-formation production for the pandemic. In two months, an increase of 76%, from 12 (19.4%) to 50 (80.64%) COVID-19 articles (n = 62, 100%) was found. The main types of articles published were editorial articles (16.13%, n = 10 of 62 articles) and commentary (9.68%, n = 6 of 62 articles). The most frequent country of origin of the scientific production was United States (12.90%, n = 8 of 62 articles), United Kingdom (12.90%, n = 8 of 62 articles), and Brazil (11.29%, n = 7 of 62 articles). However, in 2020, there were only 2 relevant randomized con-trolled trials on the COVID-19 topic in the context of physical exercise. Scientific information production shows the concern of the PA science community to bring a solution to the increase in physical inactivity generated by the COVID-19 pandemic. Our findings show the dynamics of scientific production on the COVID-19, in a situation so unique such as a pandemic, denotes that the practice of PA is essential to improve and/or maintain physical and mental health.